Synergistic combination of nanostructured sodium metal anode and capacitive cathode for advanced non-aqueous hybrid capacitors - Park, Sunwoo; Hyun, Jong Chan; Kwak, Jin Hwan; Lee, Min Eui; Jin, Hyoung-Joon; Yun, Young Soo (ELSEVIER, 2020)
Sodium metal hybrid capacitors (SMHCs) are a new type of energy storage device (ESD) composed of metal anodes and capacitive cathodes. In this study, an SMHC consisting of a nanostructure-engineered pyropolymer electrode pair is fabricated, which exhibits significantly high specific power and energy and exceptionally long lifetime. The critical obstacles of metal anodes such as the low Coulombic efficiencies (CEs) and safety problems originating from the dendritic metal growth are overcome using a stereoscopic pyropolymer thin layer including multitudinous sodiophilic sites, which can function as both electrolyte-intimate spot and nucleation catalyst. The well-designed metal anode exhibits a remarkably high average CE of similar to 99.95%, high rate capabilities up to 4 mA cm(-2), and stable cycling over 1000 cycles. In addition, the nanopore-controlled pyropolymer containing nanopores with diameters mainly of similar to 2 nm exhibits outstanding rate capabilities with a capacity retention of -60% of the initial capacity at a high current rate of similar to 50 A g(-1) in a cathodic voltage region of 1.0-4.2 V in a diglyme-based electrolyte. The nanostructure-engineered pyropolymer-based electrodes are assembled as a pair of Faradic and non-Faradic electrodes in an SMHC, which exhibits the highest specific power of similar to 85,300 W kg(-1) at 143.3 W h kg(-1) and specific energy of similar to 347.7 W h kg(-1) at 1241.8 W kg(-1) among those of the reported sodium-based ESDs. Considering the simple chemistry, cheap components, and mass-producible process, the high-performance SMHC is a very promising device for use as a power source in electric vehicles and large-scale ESDs.
Keywords: HIGH-ENERGY; LITHIUM; INTERCALATION; ELECTROLYTES; NUCLEATION; STORAGE; NANOSHEETS; GRAPHITE; GROWTH